Metabolic mapping with plasmonic nanoparticle assemblies. Issue 7 (17th March 2020) - Le, Nguyen H.; Ye, Gang; Peng, Chun; Chen, Jennifer I. L.
Abstract : Discrete plasmonic gold nanoparticle assemblies rapidly detect ATP in single cells and microenvironments without labelling, extraction, purification or separation. Abstract : A rapid and simple methodology for the biomolecular analysis of single cells and microenvironments via a stick-and-peel plasmonic sensing platform is reported. Substrate-bound assemblies of plasmonic gold nanoparticles linked by reconfigurable oligonucleotides undergo disassembly upon target binding. Changes in the light scattering intensity of thousands of discrete nanoparticle assemblies are extrapolated concomitantly to yield the mapping of local target concentrations. The methodology is completely free of labelling, purification and separation steps. We quantified the intracellular ATP levels for two ovarian cancer cell lines to elucidate the differences and cellular distribution, and demonstrated the potential of the stick-and-peel platform for mapping the microenvironment of a 2D heterogeneous surface. The portable and economical analytical platform may broaden the affordability and applicability of single-cell based analyses and enable new opportunities in clinical care such as on-site molecular pathology.